Lactoferrin-mediated targeting of oncogenic pathways for cancer chemoprevention and adjunct treatment: from mechanistic insights to clinical trials - Mobeen, Iqra; Sabitaliyevich, Uteuliyev Yerzhan; Moldagassimova, Aizat; Attar, Rukset (Archives of Pharmacy, 2024)
Genetic, genomic and proteomic analyses of cells, tissues and body fluids have generated a wealth of precious information about the intricate mechanisms which underlie carcinogenesis and metastasis. Lactoferrin, a multifunctional cationic glycoprotein, has attracted widespread appreciation because of its characteristically novel properties for cancer chemoprevention. Tumor microenvironment is a highly complicated and sophisticated ecosystem, significantly reshaped by a wide variety of treatment regimes. Therefore, lactoferrin-mediated immunostimulatory role reshapes tumor microenvironment and inhibits cancer progression. There is sufficient experimental evidence related to immunostimulatory ability of lactoferrin in tumor microenvironment. Different clinical trials have been conducted for the evaluation of clinical efficacy of lactoferrin in different cancer patients. It is necessary to carefully interpret the clinical evidence and identify the major gaps in our understanding related to the selection of group of cancer patients likely to benefit the most from the combinatorial treatment regime comprised of lactoferrin and chemotherapeutic drugs. Moreover, lack of efficacy should be analyzed by a team of interdisciplinary researchers for a broader and comprehensive understanding of the mechanisms underlying treatment failure.